Composting of food wastes: Status and challenges. (January 2018) - Cerda, Alejandra; Artola, Adriana; Font, Xavier; Barrena, Raquel; Gea, Teresa; Sánchez, Antoni
Graphical abstract: Highlights: Composting of food wastes was analysed in terms of operation and microbiology. The main challenges are gaseous emissions and non-biodegradable impurities. Microbiology of food waste composting has been studied with novel molecular tools. Gaseous emissions include greenhouse gases, ammonia and volatile organic compounds. Quality of food waste compost is related to chemical content, maturity and stability. Abstract: This review analyses the main challenges of the process of food waste composting and examines the crucial aspects related to the quality of the produced compost. Although recent advances have been made in crucial aspects of the process, such composting microbiology, improvements are needed in process monitoring. Therefore, specific problems related to food waste composting, such as the presence of impurities, are thoroughly analysed in this study. In addition, environmental impacts related to food waste composting, such as emissions of greenhouse gases and odours, are discussed. Finally, the use of food waste compost in soil bioremediation is discussed in detail.